Active Humidification With Boussignac CPAP: In Vitro Study of a New Method. - Alonso-Inigo, José M; Almela, Amadeo; Albert, Alejandro; Carratala, José M; Fas, María J (Respiratory Care, 2013)
OBJECTIVE: To carry out an in vitro study of Boussignac CPAP valve performance with a new humidification method, using a heated humidifier. METHODS: Two heated humidifiers were evaluated: Fisher & Paykel MR850, and Covidien Kendall Aerodyne 2000. Baseline measurementswere taken in all experimental conditions without humidification. The Boussignac valve was adapted to the input of the humidification chamber. The system was connected to a test lung to assess the degree of pressurization. Hygrometric and pressure measurements were performed with the followingg as flows: 10, 20, 30 and 40 L/min. RESULTS: The mean values of pressure generated by the Boussignac valve were 1.99 0.02, 6.97 0.05, 16.61 0.08 and 21.24 0.08 cm H2O, 10, 20, 30 and 40 L/min, respectively, no differences being detected between study groups. Overall absolute humidity was significantly greater with a heated humidifier than without humidification (range 40.01 0.57-25.46 0.49 compared to 0.16 0.13 mgH2O/L, P < .001). Absolute humidity was significantly higher in Kendall Aerodyne 2000 compared to MR850, regardless of the selected temperature and flow (P < .001). CONCLUSIONS: This new method of Boussignac CPAP humidification yielded humidity values above 25 mg H2O/L regardless of the heated humidifier and flow used. Pressurization values remained constant in each experimental situation and were not influenced by adding humidification. These data open up the possibility of using Boussignac CPAP on different types of patients, with different interfaces and for long periods of time